The Impact of Negative Work Gossip on Employee Performance and Emotional Exhaustion - Tri Siwi Agustina; Martinah Martinah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Negative workplace gossip drains employees’ resources, diverts energy from the task, and induces emotional exhaustion, which impairs performance. This study investigated the impact of negative workplace gossip on task performance and emotional exhaustion among employees at Soto Bang Amat, a traditional restaurant in Banjarmasin, Indonesia. The study also examined emotional exhaustion as a mediator and perceived organizational support (POS) as a moderator in this relationship. Data were collected from 50 employees using a 5-point Likert scale questionnaire, analyzed through Smart PLS 3.0. The study findings revealed that negative workplace gossip significantly reduced task performance and increased emotional exhaustion. Emotional exhaustion partially mediated the gossip-performance relationship, while POS attenuated the negative impact of gossip on performance. These results are in line with the Conservation of Resources theory, which highlights gossip as a stressor in the workplace. Practically, managers should foster a supportive environment through open communication and recognition programs to mitigate the impact of gossip. The small sample size and focus on a single site limit generalizability, thus future research with larger samples and multiple sites is recommended.